Malabsorpsi zat besi dalam anemia defisiensi besi - D. M. Mackay, D. M. Mackay (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1977)
keywords: anemia, sprue, tropical enteropathy, absorpsi zat besi,